S Senam Aerobik Benturan Ringan Menurunkan Gejala Premenopause pada Wanita - MK. Fitriani Fruitasari (Journal of Nursing Invention, 2022)
Background: Premenopause for women is the time when the body begins to experience changes or transitions to menopause. At this time there will be changes in the body, such as the decline in reproductive function, hormonal, physical and psychological changes. Symptoms that are often a complaint of premenopausal women are a burning sensation that radiates from the chest to the neck and face or often known as hot flushes, night sweats or night sweats, easy fatigue, sleep disturbances, decreased memory, easy to feel, easy to relax. and depression. One way to reduce premenopausal symptoms is to exercise, one of which is light aerobic exercise.  Objective: To identify the effect of low impact aerobic exercise on premenopausal symptoms of premenopausal women. Method: The design of this study used a pre-experimental design with Static Group Comparison/Posttest Only Control, the subjects of this study were 96 premenopausal women in Sukajaya Palembang Village. Data collection using a premenopausal symptom questionnaire. Analysis of the difference data using the independent t test.  Conclusion: The study was conducted on 96 premenopausal women and the results of the analysis showed that the premenopausal symptoms of the intervention group were lighter than the control group. Premenopausal symptoms in the intervention group and the control group showed a significant difference with a value of =0.00 (Ï<0.05).